2016
DOI: 10.1080/21645515.2016.1139253
|View full text |Cite
|
Sign up to set email alerts
|

HPV vaccination: Population approaches for improving rates

Abstract: There is evidence to support the application of the Community Preventive Services Task Force recommendations specifically to HPV vaccination both for client reminder and recall programs and for provider assessment and feedback interventions. Multiple targeted approaches will be needed to substantially impact HPV vaccine rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Black and Hispanic females also reported lower rates of healthcare provider recommendation for the HPV vaccine between 2008 and 2013 compared to white females [27]. Recently, efforts to increase vaccination among minority groups, including mitigating cost, education campaigns, and efforts to improve provider recommendation quality, appear to be successful, with vaccine initiation rates no longer differing by race/ ethnicity, although completion continues to remain low among minorities [1315, 22]. Although vaccination is improving in these groups, it is important to also consider when the vaccine is administered, as our data indicate that young black females may be initiating sex at an earlier age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Black and Hispanic females also reported lower rates of healthcare provider recommendation for the HPV vaccine between 2008 and 2013 compared to white females [27]. Recently, efforts to increase vaccination among minority groups, including mitigating cost, education campaigns, and efforts to improve provider recommendation quality, appear to be successful, with vaccine initiation rates no longer differing by race/ ethnicity, although completion continues to remain low among minorities [1315, 22]. Although vaccination is improving in these groups, it is important to also consider when the vaccine is administered, as our data indicate that young black females may be initiating sex at an earlier age.…”
Section: Discussionmentioning
confidence: 99%
“…Low vaccination rates among all females led to a series of initiatives and programs, including: health provider education and training on communication about the vaccine, increasing funding for programs offering universal vaccination, educating parents about the vaccine, and administration of HPV vaccines in schools [1315]. Although these programs have been helpful at increasing HPV vaccination among all vaccine-eligible adolescents, there is some evidence that HPV vaccination was lower among black females early after the vaccine was introduced.…”
Section: Introductionmentioning
confidence: 99%
“…(48) A recent literature review of interventions to increase HPV vaccination rates suggested that there was sufficient evidence to support the use of Community Preventive Task Force recommendations related to client reminder and recall systems as well as provider assessment and feedback. (49) Thus, future interventions may benefit from considering point-of-care reminders that simultaneously prompt physicians and patients to discuss HPV vaccination. (50)…”
Section: Discussionmentioning
confidence: 99%
“…Many barriers to completion of the HPV vaccine series are structural, including infrequent preventive health care visits during adolescence, missed clinical opportunities, poor communication about the need for multiple HPV vaccine doses, and the lack of reminder/recall systems for follow-up doses. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Overcoming barriers to HPV vaccine series completion requires a multipronged approach. Offering vaccines at convenient settings where adolescents are known to access health care services, as in school-based health centers (SBHCs), could play an important role in improving HPV vaccination coverage rates.…”
mentioning
confidence: 99%